(untitled) (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Nephrotic syndrome is a common childhood renal disorder; the prevalence of Urinary tract infection (UTI) in these patients is high. The increased prevalence of UTI is due to immunoglobulin loss, defective T cell function, presence of ascites and relative malnutrition. Objective: To determine the clinical characteristics of UTI and its antimicrobial sensitivity pattern among the children with idiopathic nephrotic syndrome. Methods: A cross-sectional study which was conducted among purposively selected 54 patients with idiopathic nephrotic syndrome in the department of pediatrics from January to June 2017 at Comilla Medical College Hospital. Data were collected by performing physical examination of the children and face-to-face interview of the parents and investigation reports using a structured questionnaire. Descriptive and bivariate analysis was done using the analytic software SPSS version 21.0. Means and standard deviations were calculated for parametric variables and means were compared using Student’s t-test. Nonparametric variables were expressed in proportions. Differences between frequencies were tested using Chi-square test, p-values <0.05 were considered significant. Results: Majority of the children was male (55.5%) hailing from a middle-class family (59.3%) with a mean age of 4.5±22 years. The prevalence of UTI among the patients was 25.9%. The clinical features associated with UTI were frequent urination (p<0.001) suprapubic tenderness (p<0.001) and dysuria (p<0.001) although a number of UTI were asymptomatic. Frequent episodes of nephrotic syndrome were associated with UTI (p<0.048) Urinalysis showed that pus cell (p=0.001) and RBC (p=00.4) were significantly associated with UTI. The common organisms isolated were E.coli (64.3%). Proteus (21.5%), Klebsiella (14.3%), Staphylococcus (7.1%) and Pseudomonas (7.1%). Majority of the common antibiotics were resistant to the organisms isolated. The highest sensitivity was for Imipenem (78.6%), Nitrofurantoin (71.4%), Cefuroxime (57 1%) and Ciprofloxacin (42.9%). Conclusion: There is a high prevalence of UTI in children presenting with nephrotic syndrome. Therefore, a routine urine cultures should be done on patients with nephrotic syndrome and appropriate antibiotics should be used. J Com Med Col Teachers’ Asso July 2025; 29(2): 119-126